Comparative analyses of catalytic degradation of PCDD/Fs in the laboratory vs. industrial conditions. (January 2018) - Zhan, Ming-Xiu; Fu, Jian-Ying; Ji, Long-Jie; Deviatkin, Ivan; Lu, Sheng-Yong
Abstract: This study investigates the efficiencies and mechanisms of the catalytic degradation of polychlorinated dibenzo-p-dioxins and furans (PCDD/Fs) first, in simulated laboratory conditions and then, in a commercial municipal solid waste incineration (MSWI) plant. Five commercially available V2 O5 -WO3 /TiO2 (VWTi) catalysts were tested. The degradation efficiency of PCDD/Fs in the simulated flue gas ranged 22.8–91.7% and was generally higher than that in the MSWI flue gas of 8.0–85.4%. The degradation efficiency of PCDD/Fs in the real flue gas of the MSWI plant was largely hindered by the complex composition of the flue gas, which could not be completely reproduced in the simulated laboratory conditions. Furthermore, the degradation of the higher chlorinated PCDD/Fs was easier compared to the lower chlorinated ones in the presence of the VWTi catalysts, which was primarily driven by the tendency of the higher chlorinated PCDD/Fs to be adsorbed on the surface of the catalyst and further destructed due to their lower vapor pressure. In addition, powdered catalysts should be preferred over the honeycomb shaped ones as they exposed higher PCDD/Fs degradation efficiencies under equal reaction conditions. The chemical composition and a range of the relevant to the study properties of the catalysts, such as surface area, crystallinity, oxidation ability, and surface acidity, were analyzed. The study ultimately supports the identification of the preferred characteristics of the VWTi catalysts for the most efficient degradation of toxic PCDD/Fs and elucidates the corresponding deactivation reasons of the catalysts. Graphical abstract: Image 1 Highlights: The PCDD/Fs degradation efficiency was systematically lower in MSWI flue gas. Higher chlorinated PCDD/Fs degraded easier in the presence of VWTi catalysts. Powdered catalysts achieve better PCDD/Fs degradation than the honeycomb ones. A wide range of properties can be used to estimate the PCDD/Fs degradation efficiency.